2021
DOI: 10.4103/ijo.ijo_227_20
|View full text |Cite
|
Sign up to set email alerts
|

The effects of active warming on perioperative inadvertent hypothermia in patients undergoing vitreoretinal surgery under local anesthesia

Abstract: Purpose: Perioperative inadvertent hypothermia (PIH) is the decrease in core temperature below 36°C. We aimed to assess whether PIH develops in patients operated under local anesthesia (ULA) for vitreoretinal surgery in the operating room and investigate active warming efficacy. Methods: Seventy-two patients were divided into two groups: Group 1 contained unwarmed patients ( n = 36), and Group 2, warmed patients ( n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The combination of active warming and passive insulation methods applied in this study in accordance with NC guidelines was effective in preventing IPH in 100% of the control group. Although no similar studies have been conducted in Turkey, a recent Turkish study (Urfalioglu et al, 2021) reported active heating methods to have positive effects on IPH. Another study (Tunc et al, 2022) that compared active heating and passive insulation methods determined active heating to be effective in preventing IPH.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of active warming and passive insulation methods applied in this study in accordance with NC guidelines was effective in preventing IPH in 100% of the control group. Although no similar studies have been conducted in Turkey, a recent Turkish study (Urfalioglu et al, 2021) reported active heating methods to have positive effects on IPH. Another study (Tunc et al, 2022) that compared active heating and passive insulation methods determined active heating to be effective in preventing IPH.…”
Section: Discussionmentioning
confidence: 99%
“…10 The occurrence of perioperative hypothermia may be related to the operation time > two hour, the intraoperative blood loss, the size of surgical wound, the use of anesthetic drugs, an age of > 60 years, or a low body mass index (BMI). 2,11,12 Current research on hypothermia primarily focuses on high-risk patients or specific types of surgery, such as hip replacement and thoracic surgeries. 13 The thermal management of thyroid surgery is often overlooked because of its small incisions, less trauma, and less bleeding.…”
Section: Introductionmentioning
confidence: 99%